2005
DOI: 10.1021/ol050095f
|View full text |Cite
|
Sign up to set email alerts
|

A Cyclopropabenzenylidenethenone (Propadienone) via a New Route to Alkylidenecycloproparenes

Abstract: Reaction of 1,1-dichloro-2,5-diphenylcyclopropabenzene 6 with Meldrum's acid 8 in the presence of pyridine leads to coupling of the cycloproparenyl cation 7 with the stabilized diketo anion 9. Subsequent, spontaneous, base-induced dehydrochlorination gives the alkylidenecyclopropabenzene 11 in a one-pot reaction. Flash vacuum thermolysis of 11 at 650 degrees C ejects acetone and carbon dioxide, giving cyclopropabenzenylidenethenone 12 that is isolated in an Ar matrix at 20 K and characterized by a strong keten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…189c Very recently, IR characterization of the cyclopropabenzenylidenethenone 91 produced by FVP was reported by Wentrup and co-workers (Scheme 54). 190 This result confirmed a previous hypothesis by Tomioka and co-workers who postulated 91 as one of the products obtained by irradiation of a bis-diazo ketone. 185 Several theoretical studies focussed on the geometry of propadienone and derivatives thereof and most of them concluded that cumulenones adopt a kinked structure.…”
Section: Cumulenones or ''Carbo-ketones''supporting
confidence: 91%
“…189c Very recently, IR characterization of the cyclopropabenzenylidenethenone 91 produced by FVP was reported by Wentrup and co-workers (Scheme 54). 190 This result confirmed a previous hypothesis by Tomioka and co-workers who postulated 91 as one of the products obtained by irradiation of a bis-diazo ketone. 185 Several theoretical studies focussed on the geometry of propadienone and derivatives thereof and most of them concluded that cumulenones adopt a kinked structure.…”
Section: Cumulenones or ''Carbo-ketones''supporting
confidence: 91%
“…It served to remind me of Nozoe's life‐long fascination with the seven‐membered ring and the tropolones in particular. Apart from the properties of all these compounds being duly assessed, extensions eventually took us to the cyclobutacyclopa derivative rocketene 22 , and the propadienone 23 that has transient existence even at low temperatures . As I noted above, Tetsuo Nozoe's interest was evident from his questions—as astute and adept as always and showing little effect of the passage of four years since first meeting him (Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…Apart from the properties of all these compounds being duly assessed, extensions eventually took us to the cyclobutacyclopa derivative rocketene 22, [21] and the propadienone 23 that has transient existence even at low temperatures. [22] As I noted above, Tetsuo Nozoe's interest was evident from his questions-as astute and adept as always and showing little effect of the passage of four years since first meeting him ( Figure 2). It was there in Toyonaka that I gained a greater insight into Nozoes's life and achievements.…”
mentioning
confidence: 90%
“…However, switching the N -sulfonyl group for an N -phenyl or N -alkyl group led to the formation of polysubstituted pyrazoles via a PtCl 4 -catalyzed [3,3] sigmatropic rearrangement/cyclization cascade (Scheme , eq 2) . As part of our ongoing efforts in expanding the synthetic utility of N -propargylic hydrazones, we prepared the N -propioloyl hydrazones and envisioned that a similar rearrangement/cyclization sequence from these structures might afford pyridazinones (Scheme , eq 3) . However, when 1 was treated with a gold catalyst, the 4-arylidenepyrazolone 2 was obtained instead of the expected pyridazinone (Scheme , eq 4). , We report herein a novel method for the synthesis of various 4-arylidenepyrazolones from N -propioloyl hydrazones by gold-catalyzed cyclization/1,3-migration cascade.…”
mentioning
confidence: 99%